Applicability of haptoglobin as a health bioindicator in beef and dairy cattle - Bastos, Bastos; Tadeu Raynal Rocha-Filho, José; Paulino Santana, Ítalo; Meyer, Roberto; Eugênio Guimarães, José (Pubvet, 2018)
Haptoglobin is the main acute phase protein in ruminants, and its use is being widely investigated in animal clinics as an early biomarker of inflammation, infection, tissue damage and stress conditions. This occurs due to the fact that this protein presents blood values close to 0.05 mg / ml in healthy cattle, but it increases more than 100 times during the pathological conditions, even before clinical signs appear and changes in the leukogram occur. Considering these characteristics, haptoglobin has a high potential for use in different areas of the Brazilian livestock industry. Thus, the aim of this literature review is to compile the scientific studies that used this protein as a bioindicator of animal health in beef and dairy cattle. In beef cattle, it was verified that the quantification of haptoglobin may contribute to the screening of animals in the ante morten inspection, allowing the identification of animals with subclinical disease that were not diagnosed by visual inspection; can also contribute to the verification of animal welfare in the moments after transportation and pre-slaughter, avoiding the slaughter of animals with possible stresses that may alter the quality of the meat products. In dairy cattle, haptoglobin can directly contribute to the identification of cows with different levels of clinical and subclinical mastitis, besides allowing the identification of lots of milk with high concentration of somatic cells or from herds affected by infectious agents. In order to promote its inclusion as a monitoring tool within the Brazilian livestock industry, for use by both veterinarians and industrial establishments of animal products, it is recommended to carry out validation studies on the use of haptoglobin as an animal health bioindicator in partnership with companies of the sector, so that its practical utility is verified directly by the professionals involved.